EXPONENTIAL STABILITY OF INTERVAL DYNAMICAL SYSTEM WITH MULTIDELAY - SUN Ji-tao(孙继涛) ZHANG Yin-ping(张银萍) LIU Yong-qing(刘永清) DENG Fei-qi(邓飞其) (Applied mathematics and mechanics, 2002)
Using the matrix measure and delay differential inequality, the sufficient conditions were obtained for exponential stability of interval dynamical system with multidelay. These conditions are an improvement and extension of the results achieved in earlier papers presented by LIAO, LIU, ZHANG, SUN, et al.